2019
DOI: 10.1111/petr.13396
|View full text |Cite
|
Sign up to set email alerts
|

Utility of neonatal donors in pediatric liver transplantation: A single‐center experience

Abstract: Background The lack of age‐ and size‐matched organs result in higher waiting list mortality in pediatric recipients than adults. Organs from deceased newborns and infants are a valuable source to increase donor pool in pediatric liver transplantation. However, the feasibility and safety of using neonatal donors have not been well evaluated. Methods From 2014 to 2016, 48 deceased donor pediatric liver transplantations with donor age younger than 1 year old in our center were enrolled in this study. The recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…One of the most important indicators for donor‐to‐recipient matching was graft‐to‐recipient weight ratio (GRWR). The ideal GRWR was 2% to 4%, and the minimal accepted ratio was 1.5% . In some patients, a GRWR >4% was also acceptable if the abdomen could be closed without tension and postoperative ultrasound showed normal blood flow.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the most important indicators for donor‐to‐recipient matching was graft‐to‐recipient weight ratio (GRWR). The ideal GRWR was 2% to 4%, and the minimal accepted ratio was 1.5% . In some patients, a GRWR >4% was also acceptable if the abdomen could be closed without tension and postoperative ultrasound showed normal blood flow.…”
Section: Methodsmentioning
confidence: 95%
“…The ideal GRWR was 2% to 4%, and the minimal accepted ratio was 1.5%. 10,11 In some patients, a GRWR >4% was also acceptable if the abdomen could be closed without tension and postoperative ultrasound showed…”
Section: Donor and Recipient Matchingmentioning
confidence: 99%
“…En-bloc renal transplantation from young donors is acceptable and safe, with a low complication rate, also in pediatric recipients [22]. Similarly, several studies have suggested that the utility of livers from donors with low body weight could be a potential strategy for increasing the availability of donors for well-selected pediatric recipients [23,24]. Moreover, kidney and liver transplantation show good results even with size and/or weight mismatched organs [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies have suggested that the utility of livers from donors with low body weight could be a potential strategy for increasing the availability of donors for well-selected pediatric recipients [23,24]. Moreover, kidney and liver transplantation show good results even with size and/or weight mismatched organs [22][23][24]. Organ size matching is more delicate for heart and lung transplantation [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Blood test and Doppler ultrasound were performed daily in the first week after surgery to monitor the recovery of graft and the condition of vessels 5 . Dual immunosuppressive therapy combining tacrolimus and steroids was applied as standard immunosuppressive strategy 6 …”
Section: Methodsmentioning
confidence: 99%